Guernsey : Report on Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Bailiwick of Guernsey has a Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) legal framework that provides the basis for an AML/CFT regime. It has a program to review and enhance AML/CFT legislation and monitor effectiveness of compliance with the AML/CFT regime. Assessors found that confiscation and provisional measures within Bailiwick are robust. They also found that previous designation mechanisms had a negative impact on the effectiveness of the mutual legal assistance system. The assessors recommended to enhance the requirements for the freezing and confiscation of terrorist assets, and also provided guidance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet